Doppelgänger/Doppeltgänger: topoi em Siebenkäs (1796), de Jean Paul Friedrich Richter e O duplo (1846), de Fiódor Mikháilovitch Dostoiévski - Marco Antônio Barbosa de Lellis (2021)
This present Thesis has by object of investigation the consecrated romantic concepts Doppelgänger and Doppeltgänger, coined by Jean Paul Friedrich Richter (1763-1825) in the work Siebenkäs, of 1796, translated by double, by those who see themselves, by replica, duplicate of themselves, look-alikes, twins, “goer, the one who wanders, walker” and, literally, “the one who walks alongside, road companion”, and affirm that they can be edified as topoi, koinoí topoi (“commonplaces”) paradigmatic to analyze the works Siebenkäs and The double and, concomitantly, the romantic irony, the satirical genre, der Witz, the laughable, the humor, the parody – since Jean Paul and Dostoevsky appropriate these literary resources for their compositions – and the actions of the main characters: the lawyer of the poor Firmian Stanislaus Siebenkäs and his friend Hoseas Heinrich Leibgeber on the one hand, and Iákov Pietróvitch Goliádkin “Senior” and his other “companion” Iákov Pietróvitch Goliádkin Second, in the novel by Fyodor Mikhailovitch Dostoevsky (1821-1881), The double, for another. The Doppelgänger, the double, the look-alike, the replica or the duplication of an another, which is always side by side, in these senses, is used to designate those characters who see themselves specularly, as if they had disposed of an another “of themselves”, like a Doppeltgänger – So heißen Leute, die sich selber sehen (“That’s what people who see themselves are called”) – walking on the same road, side by side, in a dialogical process. The relevance of the two works in the current context concentrates on the strategy that both authors use to present their social criticisms, regardless of the German and Russian sociopolitical environments, in other words, the relevance concentrates on the strategy of the Doppelgänger/Doppeltgänger, of the double, the look-alike and, by extension, the unfolding of the self.